The impact of the design of hanging advertisements on the definition of goods and products, students of the Faculties of Arts and Languages at Salah al-Din University as a model - Akram Faraedon Hamamen (Zanco Journal of Humanity Sciences)
The research's conclusions are based on the current state of development as a consequence of the factors of communication, media, technology, science, and information. As a result of this human requirement, it keeps creating new languages, specialists, and in-depth specialties in the sciences. Following the Industrial Revolution, new organizational science and art were developed in European nations by artists and activists, who then disseminated their work in the fields of business and journalism. In the present stage of life, the rules are provided to one of the human sciences, so it is continually attempted to examine it. Human sciences are always changing, and the rules are out of the same manner, aside from as a new genre in the field of media.